Evaluation on The Implementation of Study on Physical, Sport and Health in The Pandemic Time Covid-19 at SMP Negeri Se-Kota Salatiga Tapel 2020/2021 - Sanfia Tesabela Messakh; Budi Utomo; Fatkur Rohman (Universitas Negeri Medan, 2021)
The Ministry of Education and Culture of the Republic of Indonesia issued a policy to temporarily close educational activities held in schools. This policy resulted in several changes and caused a transition in the process of implementing PJOK learning. The purpose of this study is to describe the evaluation of the implementation of physical education, sports and health learning in State Junior High Schools in Salatiga during the Covid-19 pandemic. This research uses qualitative methods with a descriptive approach. The data analysis technique in this study used the Analysis Interactive Model technique from Miles and Huberman. The results of the study indicated that PJOK teachers were obliged to make learning tools such as syllabus, lesson plan (RPP), semester program (Promes) and annual program (Prota). The implementation of online learning is carried out using various internet-based applications including Google Classroom, Google From and WhatsApp (WA) as the main communication media for teachers and students for learning reminders and assignments. Learning assessments during the Covid-19 pandemic are designed to encourage meaningful learning activities for students in the form of assignments and teacher observations of students during the online learning process.